Molecular cloning of a cDNA encoding a human macrophage migration inhibitory factor. - Weiser, W Y (1989)
A cDNA encoding a human macrophage migration inhibitory factor (MIF) was isolated, through functional expression cloning in COS-1 cells, from a cDNA library prepared from a lectin-stimulated T-cell hybridoma, T-CEMB. The 115-amino acid polypeptide encoded by the MIF cDNA (p7-1) was effectively released from the transfected COS-1 cells and yielded readily detectable MIF activity in the culture supernatant despite the apparent lack of a classical protein secretory sequence. Insertional mutational analysis and elution of MIF activity from polyacrylamide gel slices demonstrated that the Mr 12,000 protein with MIF activity released by the COS-1 cells is encoded by p7-1. The p7-1 cDNA hybridized with a 700-base mRNA expressed by Con-A-stimulated lymphocytes but not unstimulated lymphocytes. The availability of the MIF cDNA clone and recombinant MIF will facilitate the analysis of the role of this lymphokine in cell-mediated immunity, immunoregulation, and inflammation.